2008
DOI: 10.1158/1055-9965.epi-07-2576
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Multiple Mailings on Recruitment: The Multiethnic Cohort

Abstract: Background: The current study considers potential nonresponse bias and data quality issues in the Multiethnic Cohort, a prospective study of lifestyle-cancer associations among adults ages 45 to 75 years from five ethnic groups in Hawaii and California. Methods: We examined determinants of early versus later response to the baseline questionnaire using logistic regression with response wave regressed on measures of demographics, history of illness, health behaviors, medication, and supplement use. Results: Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 31 publications
5
25
0
Order By: Relevance
“…A report of the PLCO (Prostate, Lung, Colorectal, and Ovarian) Cancer Screening Trial found that a small proportion of invitees enrolled, and that enrollment was higher among those who were female, white, older, and living in higher-income census blocks (Lamerato, Marcus, Jacobsen, & Johnson, 2008). These data are consistent with other reports about enrollment in cancer screening trials (Steffen et al, 2008). …”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…A report of the PLCO (Prostate, Lung, Colorectal, and Ovarian) Cancer Screening Trial found that a small proportion of invitees enrolled, and that enrollment was higher among those who were female, white, older, and living in higher-income census blocks (Lamerato, Marcus, Jacobsen, & Johnson, 2008). These data are consistent with other reports about enrollment in cancer screening trials (Steffen et al, 2008). …”
Section: Introductionsupporting
confidence: 93%
“…For example, having an experienced trial coordinator, visiting participants at home, high publicity, high perceived clinical benefit by clinicians, and practice incentives contributed to recruitment success in one study (McKinstry et al 2007). It seems that use of multiple strategies, culturally sensitive approaches, incentives, repeated invitations, and low burden on participant can enhance study enrollment (Grunfeld, Zitzelsberger, Coristine, & Aspelund, 2002; Rubin et al, 2002; Steffen et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there was little difference for missing ER status between Hispanic (24.7%) and non-Hispanic white (23.0%) women diagnosed with invasive cancer ( P  = 0.41), and overall, it is unlikely that missing ER status is associated with folate intake. The participation rate was lower in our study than for some previous studies, increasing the potential for selection bias, although obtaining high response rates in minority populations is a universal problem [77], [78]. To obtain a better understanding of the potential impact of poor response on study findings, we evaluated several factors and showed comparability for participants and non-participants [28].…”
Section: Discussionmentioning
confidence: 85%
“…In our own study, the TRacking Adolescents Individual Lives’ Survey (TRAILS), extra recruitment effort at the first measurement wave consisted of one or two house visits after no response to both an initial and a reminder letter had been received, and offering a two-month reflection period if the initial participation request was at an inconvenient time [5]. Different studies have shown that recruitment efforts lead to a more representative sample in terms of sex, age, race, socio-economic status and health [5,11,12]. Although the representativeness increases, the quality of the data has been shown to decrease with extra recruitment effort, because of more missing values and errors in data from late compared to early responders [10,12].…”
Section: Introductionmentioning
confidence: 99%